Road Traffic Fatalities in Babylon Province – Six Years Epidemiologic Study - Hasan Alwan Baiee1, Karim AL-Araji2, Ahmad Jawad Mohammed3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Road Traffic Accidents are the fifth leading cause of morbidity and mortality worldwide. In Iraq, traffic accidents are increasing continuously leading to more fatalities that rank Iraq as number four in in the world. Objectives: To assess the epidemiological features of fatal Road Traffic Accidents in a time, place, person epidemiologic model and to identify the trend of Road Traffic mortalities in Babylon - province during six years. This was a descriptive cross-sectional study included a analysis of the forensic medicine data presented in the records of forensic medicine department in Babylon Health directorate for the period 2010-2015. After the approval of the study protocol by the local health ethical committees , a structured questionnaire was used to collect data according to the descriptive epidemiologic model (person , place, time model). During the period 2010-2015 mortality rates were higher in males than females with male to female ratio of 3:1 Higher mortality rates reported in the year 2015 and the highest frequency of mortality was in the age group (16-35)years (34.9%) followed by the age group (6-15)years (14.7%) the lowest rate was among the age group(46-55) years , the highest mortalities reported among Wage earners (58.8%).